Ocular vestibular evoked myogenic potential in benign paroxysmal positional vertigo: a systematic review (Research, Society and Development, 2021)
The ocular vestibular evoked myogenic potential is reflected from extraocular muscles in response to high intensity sounds. The ocular VEMP evaluates the superior vestibular pathway and the contralateral ascending pathway, through the vestibulo-ocular reflex. Characterized by brief episodes of vertigo, nausea and / or nystagmus of positioning with a change in head position, BPPV is caused by the inappropriate presence of floating statocony particles from the utricular macula in the endolymph of the semicircular canal (s) (es) ) or bonded to the dome of the same (s). The present study aims to verify whether the latency and amplitude values ​​of the oVEMP components are different in patients with BPPV when compared to normal adults. The study is a systematic review, where it sought to investigate the latency and amplitude values ​​of oVEMP in BPPV and control group, researched in the following databases: PubMed, ScienceDirect, VHL (lilacs), SciELO, Scopus, Circumpolar Health Bibliographic Database, Embase, Web of Science and Cochrane Central Register of Controlled Trials (CENTRAL). In addition to the gray literature bases: OpenGrey, DissOnline, The New York Academy of Medicine, ClinicalEvidence.com and ClinicalTrials.gov. In the studies it is observed that the latency averages n1 and p1 in individuals with healthy BPPV and control did not show differences between yes, characterizing as normal responses. Meanwhile, the amplitude data n1 and p1 in individuals with BPPV was lower when compared to the control group. The findings point to the relevance of the approach and validate the study, since the results of the degree of latency and amplitude may suggest changes triggered by BPPV. Therefore, the oVEMP test is the most efficient to evaluate cases with BPPV.